2019
DOI: 10.1257/app.20180100
|View full text |Cite
|
Sign up to set email alerts
|

ProPelled: The Effects of Grants on Graduation, Earnings, and Welfare

Abstract: We estimate effects of the Pell Grant—the largest US federal grant for college students—using administrative data from Texas public colleges and a discontinuity in grant generosity for low-income students. Within four-year institutions, eligibility for additional grant aid significantly increases first-time students’ degree completion and later earnings. Our estimated impacts on earnings alone are enough to fully recoup government expenditures within 10 years, suggesting that financial aid likely pays for itse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 31 publications
3
33
1
Order By: Relevance
“…We find that wealth does not drive racial differences in earnings through residential sorting. However, wealth could affect earnings through other channels including borrowing constraints that limit the ability to obtain a college degree (Denning et al (2019), Stinebrickner and Stinebrickner (2008), Cameron and Heckman (2001)), to start or to expand one's business (Doorley and Pestel (2016)), or to take risk in the labor market over the course of one's career (Algan et al (2003), Bloemen and Stancanelli (2001)).…”
Section: Resultsmentioning
confidence: 99%
“…We find that wealth does not drive racial differences in earnings through residential sorting. However, wealth could affect earnings through other channels including borrowing constraints that limit the ability to obtain a college degree (Denning et al (2019), Stinebrickner and Stinebrickner (2008), Cameron and Heckman (2001)), to start or to expand one's business (Doorley and Pestel (2016)), or to take risk in the labor market over the course of one's career (Algan et al (2003), Bloemen and Stancanelli (2001)).…”
Section: Resultsmentioning
confidence: 99%
“…Even in the absence of degree completion, community college students who accrue a larger number of credits have been found to experience greater financial benefits when compared with community college students with fewer credits (Belfield & Bailey, 2011). In addition, investments in financial aid appear to make sense from a tax perspective, as previous research has reported that the positive impact of federal financial aid on students’ earnings alone is enough to recoup government expenditures within 10 years (Denning et al, 2019). For the present study, the positive impact of the information and one-course waiver treatment should be placed in its proper context—a modest increase of 1.5 percentage points in the likelihood of re-enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…In a quasi-experimental study examining the impact of community college tuition discounts on student enrollment among recent high school graduates, Denning (2017) reported that community college enrollment increased by 5.1 percentage points for each $1,000 reduction in tuition, with Black students responding more strongly to tuition discounts than White students. Although prior work has shown that the Pell Grant receipt was not associated with an increase in college enrollment (Denning et al, 2019; Kane, 1995; Rubin, 2011), grants that supplement the Pell grant are more likely to positively influence college enrollment (e.g., Bettinger, 2015; Castleman & Long, 2016). Richburg-Hayes et al (2015) conducted a randomized controlled trial to examine the impact of a one-time, performance-based scholarship on students’ likelihood of enrolling in college, finding that providing a $1,000 performance-based scholarship increased students’ likelihood of enrolling in college by 5 percentage points.…”
Section: Literature Reviewmentioning
confidence: 90%
“…37 However, aid alone may not be the answer. Recent research suggests that increased Pell Grant awards did not improve persistence and completion among community college students in Wisconsin, 38 although other research suggests increased need-based aid may improve completion at public four-year colleges in Texas 39 and Florida. 40 A synthesis of this body of research suggests the complexity of applying for need-based programs is likely to hinder their effectiveness, and states should consider simplifying their grant programs.…”
Section: The Complexities Of State Financial Aid Policiesmentioning
confidence: 97%